Pelatihan Dan Implementasi Konfigurasi Dasar Router MikroTik Untuk Meningkatkan Kompetensi Jaringan Siswa TJKT Di SMK Sasmita Jaya 2 - Zainudin; Aniq Astofa; Akrom (AMMA : Jurnal Pengabdian Masyarakat, 2026)
The rapid development of computer network technology requires vocational high school (SMK) graduates to possess competencies that align with the needs of business and industry, particularly in the field of router-based network management. One of the networking devices widely used in industry is MikroTik due to its comprehensive features, flexibility, and support for various network configuration requirements. However, based on observations conducted at SMK Sasmita Jaya 2, students of the Computer and Telecommunication Network Engineering (TJKT) program still face challenges in mastering network configuration, especially in operating MikroTik routers, implementing routing concepts, and performing network troubleshooting. This Community Service Program (PKM) aims to improve students’ networking competencies through training and implementation of basic MikroTik router configuration using a hands-on training approach. The implementation method was conducted intensively through three stages: preparation, execution, and evaluation. The training materials covered RouterOS introduction, IP address configuration, basic routing, Network Address Translation (NAT), network connectivity testing, and basic troubleshooting. Evaluation was carried out using pre-test and post-test methods to measure improvements in participants’ understanding and technical skills. The expected outcomes include improving students’ ability to independently configure computer networks, enhancing analytical and problem-solving skills, developing training modules and practical worksheets, and increasing students’ readiness to meet workforce demands in the field of computer networking.